Quality of life and experience of mothers with Down syndrome children - Chan, K.G (Universiti Malaysia Sarawak, (UNIMAS), 2015)
Mothering a child with Down syndrome (DS) could be stressful and emotionally overwhelming for some families. Children who are born with this condition are often associated with a variety of developmental delays and various congenital anomalies which require care in the hospital soon after delivery and subsequent medical follow-up. In Malaysia, the Ministry of Health reported an annual figure of more than 600 new cases of children with DS which constitutes almost a quarter of the total number of the children (below 12 years old) with newly reported disabilities (Malaysia, Ministry of Health (n.d.). Previous studies have highlighted the need to examine the multi-dimensional, holistic concept of quality of life (QoL) to determine the well-being and needs of mothers of child with disability (WHOQOL Group, 1996). There are little published studies related to experiences of mothers in Malaysia, particularly in the Borneo state of Sarawak. The purpose of the recent study was to understand the experiences of mothers having a child with DS and their perceived QOL in the local context. It also aimed to examine the relationship between mothers’ selected background variables and their perceived QOL.